Criminal Responsibility Against People Of The Crime Of Matters Is Reviewed From Article 170 Of The Criminal Law Book - Firmansyah, Rahman; G, Deny; A, Muhammad; Rahadian, Rian (DE LEGA LATA: JURNAL ILMU HUKUM, 2024)
This study examines criminal liability and judges' considerations for perpetrators of demolition based on Article 170 of the Criminal Code (KUHP), with a focus on the analysis of Decision Number 15/Pid.B/2022/PN.Kwg. Demolition is an act of violence that involves two or more people together against one or more victims, with the potential to cause serious physical injury or even death. This study aims to uncover how Criminal Liability Against Perpetrators of Demolition is Reviewed from Article 170 of the Criminal Code (Study of Decision Number: 15/Pid.B/2022/PN.Kwg) and Judge's Considerations in Deciding Cases of the Crime of Murder in Decision Number: 15/Pid.B/2022/PN.Kwg. The research method used is document analysis, by using court decision documents to examine legal considerations,  the evidence submitted, as well as other factors that affect the criminal decision-making process. The results of this study consider key aspects such as the evidence needed to prove the guilt of the perpetrators of the demolition committed by members of CSOs, as well as the influence of the number of perpetrators in the demolition, and the role of each perpetrator in the incident. This study highlights that criminal liability for perpetrators of demolition committed by members of CSOs is greatly influenced by the evidence presented at the trial, including the chronology of events, motives, and contributions of each perpetrator to the violence that occurred. The court also considers mitigating factors such as the losses incurred by the victim and the attitude of the perpetrator after the incident. The implication of this study is to deepen the understanding of the application of Article 170 of the Criminal Code in cases of rape, as well as its relevance in the context of modern criminal law. These findings make an important contribution to legal practitioners, academics, and law enforcement in understanding how the criminal justice system handles violent crimes committed together, with the hope of improving justice and the effectiveness of law enforcement in Indonesia